Performance Of Viterbi Based Detectors For Wideband Mobile Radio Channels - Mohd. Nazri Muhayiddin, (2002)
The focus of the thesis is to study the performance of outdoor wideband mobile radio systems operating at data rates of 144 kbitss and 384 kbits standardised by ITU for users in fast vehicular and walking-speed pedestrian environment respectively.